2011
DOI: 10.1007/s11307-011-0472-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Multi-pinhole Collimator for Imaging Small Animals with Different Sizes

Abstract: This collimator allows flexible single pinhole and MPH SPECT imaging for rodents, achieving high resolution and detection efficiency with minimal image artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…On other scanners, %STDs in the SPECT imaging showed small values when compared with our scanners [12], as no post-filter was used for our SPECT images. Therefore, we further confirmed that SPH, MPH and PAH produced different performances although Mok et al., examined the differences in performance between SPH and MPH in other scanners [8].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…On other scanners, %STDs in the SPECT imaging showed small values when compared with our scanners [12], as no post-filter was used for our SPECT images. Therefore, we further confirmed that SPH, MPH and PAH produced different performances although Mok et al., examined the differences in performance between SPH and MPH in other scanners [8].…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, PAH was not suitable for SPECT imaging, as it yielded SPECT images with low resolution. Although Mok et al reported that MPH was appropriate for bone scintigraphy using Tc-MDP with about 67 MBq [8], we expected that SPH would be useful with higher radioactivity because the bone scintigraphy was obtained by SPH using 99m Tc-MDP with about 100 MBq [11] and 185…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations